2020
DOI: 10.21203/rs.3.rs-93301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conflict-Related Population Health Research in Syria, 2011-2019: An Assessment of Information Gaps, Research Needs and Challenges, for The Lancet - AUB Commission on Syria

Abstract: Backgorund. While there has been a growth of research on health and the Syrian conflict, most such research covers Syrian refugees. There is limited information about the scope and focus of research on health and population inside Syria. While there are several systemtic and scoping literarure reviews of health of Syrian refugees, there has not been a sccoping review of research literature on health issues inside Syria. Methods. As part of a broader scoping review covering January 2011 to December 2019, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Research contribution by postgraduates of the different Syrian universities was similar in the current study, which was a remarkable improvement from the article published in 2011 which had reported that more than half of the Syrian publications had originated from Damascus University (10). This nding was supported as well by a recent review of the published articles from the different Syrian cities (17).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Research contribution by postgraduates of the different Syrian universities was similar in the current study, which was a remarkable improvement from the article published in 2011 which had reported that more than half of the Syrian publications had originated from Damascus University (10). This nding was supported as well by a recent review of the published articles from the different Syrian cities (17).…”
Section: Discussionsupporting
confidence: 61%
“…Starting in 2011, Syria has also had a decade-long war that severely crippled its healthcare system. This created an unfortunate, yet an important opportunity and need, for research in healthcare (17). Many facets now require further study and analysis, including the effects of lack of medicines and healthcare services accessibility, the spread of endemic diseases, and the war-related injuries.…”
Section: Discussionmentioning
confidence: 99%
“…11 The impact of this crisis on medical education in Syria has not been studied satisfactorily as most existing reports were merely descriptive studies of certain aspects of the calamity. 3,12,13 Therefore, there is a need for a quantitative and comparative analyses of the academic performance of medical students across different universities and time periods in Syria. Such analyses may provide valuable insights into the challenges and opportunities for improving medical education in Syria and other countries facing similar crises.…”
Section: Introductionmentioning
confidence: 99%
“…The health workforce capacity has been unevenly distributed across different specialties and areas of need, because of factors such as the destruction of the health care infrastructure, the overload of the system, the scarcity of job opportunities, the financial hardships, and the loss of many educators, doctors, and health care workers 11 . The impact of this crisis on medical education in Syria has not been studied satisfactorily as most existing reports were merely descriptive studies of certain aspects of the calamity 3,12,13 . Therefore, there is a need for a quantitative and comparative analyses of the academic performance of medical students across different universities and time periods in Syria.…”
Section: Introductionmentioning
confidence: 99%